Calix[4]pyrrolato aluminates: the effect of Ligand Modification on the reactivity of square-planar aluminum anions - Ebner, Fabian; Mainik, Philipp; Greb, Lutz (Chemistry - a European journal, 2021)
Structural constraint represents an attractive tool to modify p-block element properties without the need for unusual oxidation or valence states. The recently reported methyl-calix[4]pyrrolato aluminate established the effect of forcing a tetrahedral aluminum anion into a square-planar coordination mode. However, the generality of this structural motif and any consequence of ligand modification remained open. Herein, a systematic ligand screening was launched, and the class of square-planar aluminum anions was extended by two derivatives that differ in the meso-substitution at the calix[4]pyrrolato ligand. Strikingly, this modification provoked opposing trends in the preference for a Lewis acidic binding mode with σ-donors versus the aluminum-ligand cooperative binding mode with carbonyls. Insights into the origin of these counterintuitive experimental observations were provided by computation and bond analysis. Importantly, this rationale might allow to exploit mode-selective binding for catalytic rate control.
Gesehen am 20.04.2023